Development and release of a national immunization app for Canada (ImmunizeCA). Issue 14 (30th March 2015) - Wilson, Kumanan; Atkinson, Katherine M.; Penney, Greg
Abstract: Digital technology has created an opportunity to reenvision the traditional immunization paper record. We describe our experience developing a government endorsed mobile immunization record in Canada. The smartphone app, ImmunizeCA is designed to assist individuals in managing their own health information. It allows individuals to store their and their family's immunization records on their smartphone. The app, which is populated by data provided by the user, contains all 13 provincial and territorial schedules, immunization information and outbreak alerts on vaccine preventable diseases. Our experience suggests mobile apps can serve as a mechanism to empower users, increase participation in the process of immunization, potentially improve immunization rates and address jurisdictional obstacles. Key measures of success will include long term uptake, acceptability as an official record, enabling data flow permitting integration with immunization information systems and the ability to rapidly iterate to address changes to both immunization practice and mobile technology.